Recent Advances in Dielectric Chiral Metasurfaces - Zhipeng Hu; Yuwei Sun; Hongguang Dong; Houxin Fan; Kaige Ding; Yi Jin; Sailing He (Advanced Physics Research)
Abstract Natural chiral materials commonly possess weak chirality. Strong chirality can be achieved using chiral metasurfaces or metamaterials consisting of atom‐like subwavelength units. Chiral metasurfaces, as a surface layer of subwavelength units, have gained much attention recently, since they are more easily fabricated than chiral metamaterials while the strong chirality is retained. Compared with metal ones, dielectric chiral metasurfaces have low material loss and support rich localized resonance. Here, we review various dielectric chiral metasurfaces, which are classified based on the geometry configuration, including three‐dimensional chiral metasurfaces (the unit cell is not uniform along the height direction) and planar chiral metasurfaces (the unit cell is uniform along the height direction). To further enhance the chirality effect, periodic coupling may be adopted to reduce the leakage to improve the resonant quality factor and enhance the excited localized field. Various dielectric chiral metasurfaces are introduced, and their potential applications are discussed. Dielectric chiral metasurfaces provide a new and strong tool in chirality manipulation with important potential applications.